Investigation of Q Angle and Related Factors in Osteoporosis Patients - Basgun, Nurseda; Elbasti, Muhammet Sahin; Yentu, Songul Baglan (Aves, 2025)
Background: The aim of this study was to examine the Q angle in patients diagnosed with osteoporosis, osteopenia, and osteoarthritis and to compare the groups with each other. Methods: This study included 22 female patients diagnosed with osteoporosis, 22 female patients diagnosed with osteopenia, and 22 female patients diagnosed with osteoarthritis, aged 40-65 years. Q angle, pain, lower extremity muscle strength, foot posture, and pes planus were assessed using a goniometer, Visual Analog Scale (VAS), Medical Research Council (MRC) Scale, Foot Posture Index (FPI), and Navicular Drop Test (NDT), respectively. Results: There was a statistical difference in both right and left Q angle in osteoporosis compared to osteoarthritis (P=.009, P=.002, respectively). There was no statistically significant difference in both right and left Q angle between osteoporosis and osteopenia (P=.730, P=.491, respectively), and osteopenia and osteoarthritis (P=.022, P=.017, respectively). However, a statistically significant difference was found between osteoporosis and osteoarthritis in the right (P=.009) and left (P=.002) sides. In addition, a significant negative correlation was found between Q angle and FPI and NDT in all patients in this study (P < .01). Conclusion: Patients with osteoporosis were found to have a higher Q angle than osteoarthritis and osteopenia patients. In addition, foot posture and pes planus were found to be associated with the Q angle. Osteoporosis patients may have a tendency to valgum.
Keywords: Osteoarthritis; osteopenia; osteoporosis; Q angle